Efficacy and safety of ruxolitinib in adult patients with refractory rheumatic disease-associated macrophage activation syndrome - Li, Jingjing; Wang, Ran; Chen, Jie; Xu, Antao; Fu, Yakai; Lin, Yanwei; Wang, Xiaodong; Ye, Shuang; Yuan, Ye; Du, Fang; Fu, Qiong (Frontiers in Immunology, 2025)
ObjectiveRheumatic disease-associated macrophage activation syndrome (RD-MAS) is a rare and life-threatening complication of rheumatic diseases, with approximately 30% of cases being refractory to conventional therapeutic protocols. Ruxolitinib, a Janus kinase 1/2 inhibitor, has emerged as a potential therapy for refractory RD-MAS. This study aimed to evaluate its efficacy and safety in patients with refractory RD-MAS.MethodsA meticulous chart review was conducted on 20 refractory RD-MAS patients treated with ruxolitinib. Data from no ruxolitinib treatment RD-MAS patients served as historical controls. Clinical and laboratory parameters, therapeutic response, and survival outcomes were analyzed. Ruxolitinib’s efficacy and safety were evaluated, and survival rates were compared to historical controls.ResultsThe cohort included 20 refractory RD-MAS patients (17 females, 3 males) with underlying conditions: adult-onset Still’s disease (n = 13), systemic lupus erythematosus (n = 4), and other connective tissue diseases (CTDs) (n = 3). All patients displayed active disease at baseline. By week 8, 50% (10/20) of patients achieved partial remission, while 30% (6/20) attained complete remission. The ruxolitinib group had a significantly higher survival rate (19/20, 95%) compared to historical controls (13/21, 62%) (P = 0.011). By week 8, the median daily glucocorticoid dose dropped from 2.7 mg/kg to 0.5 mg/kg. Cytomegalovirus infection occurred in 20% (4/20) of patients.ConclusionRuxolitinib demonstrated substantial efficacy and tolerability in refractory RD-MAS, improving clinical outcomes and reducing glucocorticoid dependence. Although limited by its retrospective nature and small cohort size, this study suggests that ruxolitinib may serve as a potential therapy for refractory RD-MAS, warranting further investigation.